(untitled) (Malaysian Journal of Fundamental and Applied Sciences, 2017)
Lattice energy is the energy needed to form crystals of a compound from the individual molecules. It is related to the stability of a compound in the solid state. In this study, systematic cluster method has been applied to obtain the lattice energy of urea. Using this method, the effect of solid state environment is included in a systematic way. Starting from the small clusters containing a few molecules, the largest cluster we studied contains 84 molecules. In order to improve the results from the cluster method using Gaussian 09 program, correction using the D3BJ program was included. The results show that, when compared to the experimental value, the lattice energies obtained were under-estimated for all the theoretical levels considered. Generally, application of the systematic cluster method shows decrease in calculated lattice energy as more molecules were included in the clusters and becomes closer to the experimental value of urea. Of all the levels considered, B3LYP/DEF2-TZVP with correctional terms provides the closest value to the one from the experiment.